Elucidating the role of interfacial MoS2 layer in Cu2ZnSnS4 thin film solar cells by numerical analysis - Ferdaous M.T.; Shahahmadi S.A.; Chelvanathan P.; Akhtaruzzaman M.; Alharbi F.H.; Sopian K.; Tiong S.K.; Amin N. (Elsevier Ltd, 2023)
Alignment; Charge carriers; Computer software; Copper compounds; Efficiency; Electron affinity; Energy gap; Heterojunctions; Layered semiconductors; Molybdenum compounds; Numerical analysis; Semiconductor doping; Solar cells; Thin film solar cells; Thin films; Tin compounds; Transition metals; Cell performance; Cu2ZnSnS4; Czts solar cells; Higher efficiency; Interfacial layer; Layer thickness; Metal-semiconductor junctions; Transition metal dichalcogenides; Zinc compounds; electron; energy efficiency; film; numerical method; simulation; software; solar power; transition element